AREAS OF PROSPECTIVE IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE IN UZBEKISTAN USING THE EXAMPLE OF THE FINANCIAL SPHERE - Karimov Diyor Mukhtarovich; Bakhshalieva Ursula Fyarshadovna (Journals Park Publishing, 2025)
This article analyzes promising areas for the implementation of artificial intelligence (AI) in the financial sector of Uzbekistan. In the context of rapid technological development and global digitalization, AI is becoming a key tool for improving the efficiency of various sectors of the economy and social sphere. The article discusses several key areas where the use of AI can lead to significant improvements. It emphasizes the need to create a favorable infrastructure and educational base for training specialists in the field of AI, as well as the importance of cooperation with international organizations and the private sector for the implementation of projects. In conclusion, the author concludes that the successful implementation of AI in Uzbekistan can become a catalyst for economic growth and social progress, contributing to the sustainable development of the country in the face of global challenges.
Keywords: Artificial intelligence, AI, economy, threat, financial sphere, tax sphere, customs sphere, healthcare, agriculture, energy, international cooperation, innovation, Uzbekistan, strategy - 2030.